Identification of Landfill Site by Using Geospatial Technology and Multi Criteria Method- A Case Study of Kathmandu, Bhaktapur and Lalitpur District of Nepal - Basnet, Deepa (International Journal of Environment, 2015)
Landfill is a mode of municipal solid waste disposal. Thus, it is imperative to select relevant site for land filling in order to curtail environmental damage and harmful impacts on wellbeing of public. Through the decades, rummage around various places for landfill site has been going on concerning its distance from artery road, resident area and water surface in order to prevent serious health and environmental hazards. In case of Nepal, Sisdole landfill site at Okharpauwa VDC in Nuwakot is struggling to manage garbage produced by the Kathmandu valley. The valley alone mounds to 700 metric tons of garbage on a daily basis that would loosened carrying capacity of the place really soon. With the intention of uncovering suitable site for alternative to present disposal site, the Multi criteria method has been applied in GIS domain. Here, data layers of land use pattern, residential areas, urban areas, roads and water bodies of the Kathmandu, Lalitpur and Bhaktapur district were mainly considered. The buffer zones were created to those 5 layers assigning various decisive factors to determine area around them within a certain distance. Then, weightings were assigned to each criterion as per their relative importance and ratings. Furthermore, weights were integrated in GIS environment to generate suitable site. Lastly, comparative study of data layers suggested that next site for dumping refuse could be the Bhaktapur district. DOI: http://dx.doi.org/10.3126/ije.v4i1.12183 International Journal of Environment Volume-4, Issue-1, Dec-Feb 2014/15, page : 121-129